PENERAPAN SANKSI PIDANA TERHADAP PERUSAHAAN YANG TIDAK MELAKSANAKAN REKLAMASI PASCA TAMBANG DI KABUPATEN KUTAI KARTANEGARA (TINJAUAN UNDANG-UNDANG NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGAN MINERAL DAN BATU BARA) - Dedi Setiawan (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTION Dedi Setiawan, 11.11.1001.1011.151. Application of Criminal Sanctions Against Company That Do Not Perform Post-Mining Reclamation At Kutai (Review of Law No. 4 of 2009 on Mineral and Coal Mining).thesis. Law, Faculty of Law, University of August 17, 1945. 2015 Supervisor I :. Prof.H.Sarrosa Hamong Pranoto, SH, .M.Hum and Supervisor II :. Isnawati, SH, .MH This study aims to find out about the application of criminal sanctions against companies that do not carry out reclamation and mine closure in Kutai, which in this study aims to discuss the application of criminal sanctions against against companies that do not carry out the post-mining reclamation review of Law No. , 4 on Mineral and Coal. This study uses empirical methods. Source of data used are primary data and secondary data. It can be concluded that the application of criminal sanctions against companies that do not carry out the post-mining reclamation and regulated in Law No. 4 of 2009 on Mineral and Coal and its implementation has been stipulated in Government Regulation of the Republic of Indonesia Number 78 Year 2010 About the Mine Reclamation and pacsa. The government revoked the license either through a written warning, suspension of operations until revocation of IUP, IUPK, or IPR. According to the results of research in Kutai there are companies that do not carry out the post-mining reclamation because the majority of companies are still actively mined.